Inferior medial genicular artery pseudoaneurysm after primary total knee arthroplasty: a case report - Ahmed M. Abdelaal; Ahmed A. Khalifa (Travmatologiâ i Ortopediâ Rossii)
Background. Small genicular vessel injuries during primary total knee arthroplasty can pass unnoticed during the surgery and present late postoperatively.